`F(s) = ln ln s` Differentiate the function.

Expert Answers
sciencesolve eNotes educator| Certified Educator

You need to differentiate the function with respect to variable s, using the chain rule, such that:

`F'(s) = (ln ln s)'`

`F'(s) = ln'(ln s)*(ln s)'*(s)'`

`F'(s) = 1/(ln s)*(1/s)*1`

`F'(s) = 1/(s*ln s)`

Using the power property of logarithms, yields:

`F'(s) = 1/(ln s^s)`

Hence, evaluating the derivative of the given function, yields `F'(s) = 1/(ln s^s).`

Access hundreds of thousands of answers with a free trial.

Start Free Trial
Ask a Question